The Arts of Media Writing / An Empirical Study on the Privacy of Media Writing - شطاح محمد (ALBAHITH ALALAMI, 2014)
Media writing is accuracy writing. Clarity and concision are its predominant features. It is a writing that goes straight to the essence because it has no time to waste. Furthermore, it must be as accurate as scientific writing. It is destined for the average reader and has to be understood by everyone. However, it can be as elegant as literary writing. The variety in its forms of expression does not prevent media writing from having its own amplitude. In short, this study is a practical approach that aims at studying different kinds of writing styles and identifying the specificity of media writing using some patterns and examples